2018
DOI: 10.1016/j.jvolgeores.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Petrophysical properties of volcanic rocks and impacts of hydrothermal alteration in the Guadeloupe Archipelago (West Indies)

Abstract: The GEOTREF project aims at developing high enthalpy geothermal energy in fractured reservoirs. It focuses on active volcanic islands and especially on the Basse-Terre Island (Guadeloupe archipelago). As part of this project we measured several petrophysical properties to better understand how fluids flow in the hydrothermal system, provide a set of parameters to modelers and build dataset for the future interpretation of * Corresponding author at: UMR 7359 GeoRessources, Ecole Nationale Supérieure de Géologie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 99 publications
3
28
0
Order By: Relevance
“…Several authors have focused their petrographic and geochemical studies on fresh volcanic rocks of the southern active volcanic part of the archipelago, and most of the studies have concentrated further south or near La Soufrière volcano or Bouillante geothermal field providing a revision of the ages of the volcanic formations and the lithological contours Dagain, 1981;Blanc, 1983;Boudon et al, 1989;Samper et al, 2007Samper et al, , 2009Patrier et al, 2013;Verati et al, 2014;Ricci et al, 2017). A recent study has shown the evolution of petrophysical properties from fresh to hydrothermalized volcanic rocks in the volcanic island of Guadeloupe archipelago (Navelot et al, 2018).…”
Section: Guadeloupe In the Lesser Antilles Geological Contextmentioning
confidence: 99%
“…Several authors have focused their petrographic and geochemical studies on fresh volcanic rocks of the southern active volcanic part of the archipelago, and most of the studies have concentrated further south or near La Soufrière volcano or Bouillante geothermal field providing a revision of the ages of the volcanic formations and the lithological contours Dagain, 1981;Blanc, 1983;Boudon et al, 1989;Samper et al, 2007Samper et al, , 2009Patrier et al, 2013;Verati et al, 2014;Ricci et al, 2017). A recent study has shown the evolution of petrophysical properties from fresh to hydrothermalized volcanic rocks in the volcanic island of Guadeloupe archipelago (Navelot et al, 2018).…”
Section: Guadeloupe In the Lesser Antilles Geological Contextmentioning
confidence: 99%
“…The distribution and type of porous and mineral phases are key for understanding waves speeds and rock strength. Although igneous volcanic rocks have been studied in terms of their porosity, permeability and seismic character (Adam and Otheim ; Adelinet et al ; Benson et al ; Heap et al ; Rossetti et al ; Vanorio et al ; Vinciguerra et al ), and alteration (Adam et al, ; Christensen & Salisbury, ; Heap et al, ; Kanakiya et al, ; Mordensky et al, ; Navelot et al, ; Pola et al, ; Wyering et al, ), little knowledge involves the effect of rock alteration and fractures on elastic waves speed for volcaniclastic rocks. Here we study at atmospheric and reservoir pressures how rock alteration influences the development of porosity and rock density and its impact on wave speeds for volcaniclastic and intrusive rocks within the Ngatamariki geothermal field, New Zealand (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of wave speeds and porosities on altered volcanic rocks have been performed at atmospheric pressures. Pola et al () investigate physical properties of altered volcanic rocks collected from outcrops, and Navelot et al () study altered lavas and debris flows but only fresh pyroclastic rocks. Wyering et al () study the physical properties of rocks of variable lithology and alteration in the Taupo Volcanic Zone (TVZ).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5 describes the simplified rock types that we used to represent subsurface heterogeneities. We define five rock types with petrophysical properties that follow the findings of Navelot et al (2018). The following three rock types are used to define the base geology of the model:…”
Section: Parametrization Of the Modelmentioning
confidence: 99%